2015
DOI: 10.3389/fphar.2015.00050
|View full text |Cite
|
Sign up to set email alerts
|

Rodent models to study the metabolic effects of shiftwork in humans

Abstract: Our current 24-h society requires an increasing number of employees to work nightshifts with millions of people worldwide working during the evening or night. Clear associations have been found between shiftwork and the risk to develop metabolic health problems, such as obesity. An increasing number of studies suggest that the underlying mechanism includes disruption of the rhythmically organized body physiology. Normally, daily 24-h rhythms in physiological processes are controlled by the central clock in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 94 publications
2
72
0
3
Order By: Relevance
“…Shift workers who work from 10 pm to 6 am make up about 20% of working force in modern society (Antunes et al, 2010) and have a higher prevalence of obesity and heart disease (Karlsson et al, 2001; Kubo et al, 2011; Suwazono et al, 2008). Dim light at night or prolonged daily light exposure promotes obesity and metabolic disorders in animal models (Aubrecht et al, 2015; Kooijman et al, 2015; Opperhuizen et al, 2015). Housing mice under constant light caused arrhythmicity in locomotor activity, increased food intake, reduced energy expenditure, increased body fat mass, and impaired insulin sensitivity (Coomans et al, 2013a; Shi et al, 2013).…”
Section: Evidence Supporting a Role Of Central Clock In Energy Metabomentioning
confidence: 99%
“…Shift workers who work from 10 pm to 6 am make up about 20% of working force in modern society (Antunes et al, 2010) and have a higher prevalence of obesity and heart disease (Karlsson et al, 2001; Kubo et al, 2011; Suwazono et al, 2008). Dim light at night or prolonged daily light exposure promotes obesity and metabolic disorders in animal models (Aubrecht et al, 2015; Kooijman et al, 2015; Opperhuizen et al, 2015). Housing mice under constant light caused arrhythmicity in locomotor activity, increased food intake, reduced energy expenditure, increased body fat mass, and impaired insulin sensitivity (Coomans et al, 2013a; Shi et al, 2013).…”
Section: Evidence Supporting a Role Of Central Clock In Energy Metabomentioning
confidence: 99%
“…There are various animal models to mimic human shift work, including altering the timing of food intake, activity, sleep, or light exposure . Disruption of the light‐dark cycle has been shown to disrupt metabolic processes and have profound effects on mammalian physiology, however, the effect of a disrupted light‐dark cycle on gastric vagal afferent satiety signaling remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in animals report inconsistent results regarding food intake during day- and night-shift work. A review of animal models of shift work and effects on metabolism found that effects depended on the species examined (rat or mouse) and the protocol used (manipulate timing of activity, light, food intake, and/or sleep) [21]. In human night workers, a recent meta-analysis reported no change in total calorie intake [26], although there are many other documented changes, such as timing of food intake, number, size, and nutritional content of meals [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although several animal models indicate marked metabolic changes due to rest-work [21], only models involving relatively extreme rest-work schedules have been applied so far. The early metabolic effects of simulated night-shift work have yet to be investigated in animal models.…”
Section: Introductionmentioning
confidence: 99%